(NON) conventional approaches applied to the study of brazilian aquifers - Bonotto, Daniel Marcos [UNESP]; De Oliveira, Edson Gomes [UNESP] (My University, 2010)
The Earth's water is always in movement, and the water cycle describes the continuous movement of water on, above, and below the surface of the Earth. Thus, the water cycle describes the processes that drive the movement of water throughout the hydrosphere, whilst a reservoir represents the water contained in different steps within the cycle. In general, there is a relationship between the mineral composition of natural water and that of the solid minerals with which the water has been in contact. This relationship may be comparatively simple and uncomplicated, as in the case of an aquifer receiving direct recharge by rainfall and from which water is discharged without contacting any other aquifer or other water. This new book discusses how different techniques can be utilized to investigate the water movement in different aquifer systems occurring in Brazil.